2017
DOI: 10.1038/srep40172
|View full text |Cite
|
Sign up to set email alerts
|

Gd(III)-induced Supramolecular Hydrogelation with Enhanced Magnetic Resonance Performance for Enzyme Detection

Abstract: Here we report a supramolecular hydrogel based on Gd(III)-peptide complexes with dramatically enhanced magnetic resonance (MR) performance. The hydrogelations were formed by adding Gd(III) ion to the nanofiber dispersion of self-assembling peptides naphthalene-Gly-Phe-Phe-Tyr-Gly-Arg-Gly-Asp (Nap-GFFYGRGD) or naphthalene-Gly-Phe-Phe-Tyr-Gly-Arg-Gly-Glu (Nap-GFFYGRGE). We further showed that, by adjusting the molar ratio between Gd(III) and the corresponding peptide, the mechanical property of resulting gels co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Similar to many self-assembly peptide molecules, it is well known that Nap-Gly-Phe-Phe (Nap-GFF) peptide sequence could drive the force of self-assembly by π−π interaction because of the benzene rings in the structure of phenylalanine and aromatics group on Nap. 37 However, as glycine and phenylalanine are hydrophobic amino acids, the solubility of peptide with the sequence of Nap-GFF is poor in water. 26 In this work, we utilized the self-assembly capability of Nap-GFF sequence and further improved the solubility by adding lysine (K) with an amino group and histidine (H) with imidazole to the Nap-GFF sequence.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to many self-assembly peptide molecules, it is well known that Nap-Gly-Phe-Phe (Nap-GFF) peptide sequence could drive the force of self-assembly by π−π interaction because of the benzene rings in the structure of phenylalanine and aromatics group on Nap. 37 However, as glycine and phenylalanine are hydrophobic amino acids, the solubility of peptide with the sequence of Nap-GFF is poor in water. 26 In this work, we utilized the self-assembly capability of Nap-GFF sequence and further improved the solubility by adding lysine (K) with an amino group and histidine (H) with imidazole to the Nap-GFF sequence.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar to many self-assembly peptide molecules, it is well known that Nap-Gly-Phe-Phe (Nap-GFF) peptide sequence could drive the force of self-assembly by π–π interaction because of the benzene rings in the structure of phenylalanine and aromatics group on Nap . However, as glycine and phenylalanine are hydrophobic amino acids, the solubility of peptide with the sequence of Nap-GFF is poor in water .…”
Section: Resultsmentioning
confidence: 99%
“…Self-assembling peptides containing D-amino acids are more stable because natural proteases can readily degrade L-form peptide bonds, but cannot degrade D-form peptide bonds. [26][27][28][29] A recent study revealed that self-assembling peptide hydrogels with β-sheet structures, made of D-amino acids, exhibit high resistance against enzymatic hydrolysis. 30 The conjugation of bioactivity-mimicking peptides to the backbone of self-assembling β-sheets derived from D-amino acids may result in improved biostability and bioactivity for potential therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[131,133135] The subsequent hydrogel formation requires retention of these aligned structures and their assembly which is usually achieved by the addition of ions or pH change. [131,136] The switchable nature of the magnetic field coupled with the slow diffusion of ions enables precise control of the anisotropy across the networks, something that is generally very difficult to achieve.…”
Section: Physical Stimuli-responsive Hydrogelsmentioning
confidence: 99%